2014
DOI: 10.3389/fmicb.2014.00416
|View full text |Cite
|
Sign up to set email alerts
|

Genome-scale data suggest reclassifications in the Leisingera-Phaeobacter cluster including proposals for Sedimentitalea gen. nov. and Pseudophaeobacter gen. nov.

Abstract: Earlier phylogenetic analyses of the marine Rhodobacteraceae (class Alphaproteobacteria) genera Leisingera and Phaeobacter indicated that neither genus might be monophyletic. We here used phylogenetic reconstruction from genome-scale data, MALDI-TOF mass-spectrometry analysis and a re-assessment of the phenotypic data from the literature to settle this matter, aiming at a reclassification of the two genera. Neither Phaeobacter nor Leisingera formed a clade in any of the phylogenetic analyses conducted. Rather,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
45
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 77 publications
5
45
0
Order By: Relevance
“…For instance, horizontal gene transfer is known as a cause of topological conflict between analyses of single genes and has even been be used to argue against hierarchical classification (Bapteste and Boucher, 2009; Klenk and Göker, 2010). However, adding more genes, up to virtually all genes available in a genome, increases support in phylogenomic analyses (Breider et al, 2014), indicating that there is a strong hierarchical signal. In contrast, selection of few genes (or any number of characters not on the same order of magnitude as the overall number of genomic characters) can hardly be called genome-scale and also depends on assumptions about the relative suitability of genes for the analysis (Lienau and DeSalle, 2009; Klenk and Göker, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, horizontal gene transfer is known as a cause of topological conflict between analyses of single genes and has even been be used to argue against hierarchical classification (Bapteste and Boucher, 2009; Klenk and Göker, 2010). However, adding more genes, up to virtually all genes available in a genome, increases support in phylogenomic analyses (Breider et al, 2014), indicating that there is a strong hierarchical signal. In contrast, selection of few genes (or any number of characters not on the same order of magnitude as the overall number of genomic characters) can hardly be called genome-scale and also depends on assumptions about the relative suitability of genes for the analysis (Lienau and DeSalle, 2009; Klenk and Göker, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The anaerobic Bacteroidia used to be considered separate from the aerobic groups such as Flavobacteriia and Cytophagia , but 16S rRNA gene sequencing clarified their interconnections (Paster et al, 1985; Weisburg et al, 1985; Woese, 1987). Despite its usefulness in resolving such taxonomic questions, the 16S rRNA gene contains only a limited number of characters and thus usually yields only partially resolved phylogenies, i.e., trees with many statistically unsupported branches (Klenk and Göker, 2010; Breider et al, 2014). Recently, Munoz et al (2016) revised the phylogeny of Bacteroidetes and removed the incertae sedis taxa from the Balneola group and Rhodothermaceae ( Bacteroidetes Order II.…”
Section: Introductionmentioning
confidence: 99%
“…Strains within this group share >89% identity of the 16S rRNA gene (Brinkhoff et al , 2008; Luo and Moran, 2014) but a reliable delineation of this group from other Rhodobacteraceae cannot be carried out with this gene (Breider et al , 2014), as branch support and other rationales for suggested 16S rRNA gene-derived Rhodobacteracea e lineages (Pujalte et al , 2014) are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…16S rRNA gene analysis places strain Y4I within the Phaeobacter genus; however, the researchers who published a recent genome-scale study (39) suggested that a formal reclassification of this genus may be forthcoming. We have previously demonstrated that indigoidine production is an exclusively surface-attached phenotype in Y4I and that its production allows this strain to outcompete Vibrio fischeri for surface niches in coculture (28).…”
mentioning
confidence: 99%